Exploring the Effect of Religious Piety on Corporate Governance: Evidence from Anti-takeover Defenses and Historical Religious Identification - Chintrakarn, Pandej (Journal of business ethics, 2017)
Because religious piety induces individuals to be more honest and risk averse, it makes managers less likely to exploit shareholders, thereby mitigating the agency conflict and potentially influencing governance arrangements. We exploit the variation in religious piety across the U.S. counties and investigate the effect of religious piety on anti-takeover provisions. Our results show that religious piety substitutes for corporate governance in alleviating the agency conflict. Effective governance is less necessary for firm with strong religious piety. As a result, religious piety leads to weaker governance, as indicated by more anti-takeover defenses. We exploit historical religious piety as far back as 1952 as our instrumental variable. Religious piety from the distant past is unlikely correlated with current corporate governance directly, except through contemporaneous religious piety. Our instrumental variable analysis, which is far less vulnerable to endogeneity, corroborates the conclusion.